Crystal structure of the putative peptide‐binding protein AppA from Clostridium difficile. Issue 4 (5th April 2019) - Hughes, Adam; Wilson, Samuel; Dodson, Eleanor J.; Turkenburg, Johan P.; Wilkinson, Anthony J.
Abstract : Cd OppA and Cd AppA are putative extracellular peptide‐binding proteins serving cognate ABC transporters in Clostridium difficile . Using purified proteins, no evidence was found for (i) peptide binding to either protein in Thermofluor experiments or (ii) the presence of peptides in the crystal structure of Cd AppA. Further sequence analysis suggests that Cd OppA is a nickel‐transporter protein and that Cd AppA may be involved in the transport of a restricted set of peptides. Abstract : Peptides play an important signalling role in Bacillus subtilis, where their uptake by one of two ABC‐type oligopeptide transporters, Opp and App, is required for efficient sporulation. Homologues of these transporters in Clostridium difficile have been characterized, but their role, and hence that of peptides, in regulating sporulation in this organism is less clear. Here, the oligopeptide‐binding receptor proteins for these transporters, Cd AppA and Cd OppA, have been purified and partially characterized, and the crystal structure of Cd AppA has been determined in an open unliganded form. Peptide binding to either protein could not be observed in Thermofluor assays with a set of ten peptides of varying lengths and compositions. Re‐examination of the protein sequences together with structure comparisons prompts the proposal that Cd AppA is not a versatile peptide‐binding protein but instead may bind a restricted set of peptides. Meanwhile, Cd OppA is likely to be the receptor protein for a nickel‐uptake system.